1973
DOI: 10.1016/0305-0491(73)90265-4
|View full text |Cite
|
Sign up to set email alerts
|

Pigments of a color polymorphism in a cichlid fish

Abstract: Abstract-i. Cichlasoma citrinellum occurs as gray or gold morphs in lakes in Nicaragua. The gold morph is variable and individuals range from yellow to dark orange.2. The pigments responsible for the carotenoid coloration are E-carotene and canthaxanthin. The gray morph contains a carotenoid component and also heavy melanin deposits.3. The carotenoids are dietary in origin, but their distribution and intensity is presumably under genetic control.4. The relation of color morphs to the ecological and selective f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
5

Year Published

1979
1979
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
1
16
1
5
Order By: Relevance
“…Though there is an environmental (e.g. diet) component to the brightness of the gold morph (Webber et al 1973), amelanism is under genetic control (Henning et al in press). Gold morphs are found in moderate to low frequencies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Though there is an environmental (e.g. diet) component to the brightness of the gold morph (Webber et al 1973), amelanism is under genetic control (Henning et al in press). Gold morphs are found in moderate to low frequencies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The larvae contained the highest amounts of carotenoids (1.738 µg/g wet weight) while non-fertilised eggs were the poorest in carotenoids (0.364µg/g wet weight). (Savolainen and Gyllenberg, 1970), while e-carotene was found in Cich"/asoma citrinellum (Webber et al, 1973) and in some other fish species, e.g., Cyprinus carpio (Czeczuga, 1979 c), S. gaudneri and trutta morpha fario (Czeczuga, 1979 b) as well as in such marine species as Limanda limanda andPlatichthys fiesus (Czeczuga, 1980). 4'-hydroxyechinenone is a derivative of echinenone; both were previously found in some salmonids, both freshwater (Czeczuga, 1979b;Matsuno et al, 1980 b) and marine (Matsuno et al, 1980 b;Czeczuga, 1982).…”
Section: Resultsmentioning
confidence: 99%
“…Changing in the density of these chromatophores, the color of the fish body can be changed accordingly. The presence of the melanic chromatophores usually masks the appearance of the xanthophores, but with the complete disappearance of the former from any region of the fish body, xanthophores became revealed (Webber et al, 1973) and the case known as xanthochromism. In such condition, the chromatophores contain E-carotene and canthaxanthin and import a golden colour (Webber et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the melanic chromatophores usually masks the appearance of the xanthophores, but with the complete disappearance of the former from any region of the fish body, xanthophores became revealed (Webber et al, 1973) and the case known as xanthochromism. In such condition, the chromatophores contain E-carotene and canthaxanthin and import a golden colour (Webber et al, 1973). It has been suggested that xanthophores may even be over-produced in the absence of melanophores or other pigment cells (Angus and Blanchard, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation